Psychoeducational programme to improve the quality of visits during family foster care: a birth and foster care family approach. - Bernedo-Muñoz, Isabel María; González-Pasarín, Lucía (My University, 2023)
Scientific literature and international and national legislation recognise the benefits of visits between foster children and their families for, among other things, maintaining emotional bonds, as well as promoting the construction of their identity and personal and family history. The research carried out by the Foster Care and Adoption Research Group of the University of Malaga on visits during family foster care had highlighted the need to improve the quality of such contacts and to support all those involve. To this end, the research group has developed and implemented in pilot phase the first Spanish psychoeducational programme Visits: a context for family development (Bernedo et al., 2020). The programme has two training modules, one for each family (birth and foster family), in which parental, educational and emotional competencies related to contact are worked on. Each module comprise seven sessions, the first six are individual and the last one in group format, to consolidate what has been learned and provide an opportunity to share feedback. The implementation of the programme includes the educational tool My Visits Book. It was designed to be used by children in foster care in collaboration with both families. The Book offers children an opportunity to share with their foster family, memories and experiences from their life before being taken into care. Likewise, to share with their birth family information about their day-to-day life with the foster family during visits. The information can be in photographs, drawings or letters format. The programme is a resource for child welfare professionals to improve the quality of visits during family foster care and to promote positive parenting in both families (birth and foster care).
Keywords: Acogimiento familiar; Familia; Psicología de la educación; Foster care family; Birth family; Psichoeducative Programme; Contact